Fraudulent Income Overstatement on Mortgage Applications During the Credit Expansion of 2002 to 2005 - Mian, Atif; Sufi, Amir (Review of Financial Studies, 2017)
Treating fraudulently overstated income on mortgage applications as true income can lead to incorrect conclusions on the nature of the mortgage credit supply expansion toward marginal borrowers from 2002 to 2005. A positive gap between zip-code-level income growth calculated from mortgage applications and income growth from the IRS likely reflects mortgage fraud, not an improvement in home-buyer income. In support of the credit supply view, mortgage credit for home purchase expanded significantly more in low-credit-score neighborhoods on both the extensive and intensive margins from 2002 to 2005, even though these neighborhoods deteriorated on many measures of income prospects.